Teacher learners theorizing from practice: A case of the concept of learner engagement in interactive second language learning tasks - Nguyen, Mai Xuan Nhat Chi; Dao, Phung; Iwashita, Noriko; Spinelli, Franciele (Teaching and teacher education, 2023)
This study investigated second language (L2) teacher learners' abilities to theorize from practice and their perceptions of this theorizing experience. Fifty-four L2 teacher learners completed a theorizing task probing for their conceptualization of ‘learner engagement’. Focus-group interviews were later conducted with 17 participants. Findings show that the teacher learners were able to generate their theories of learner engagement, which strongly aligned with expert conceptualizations. Notably, their personal theory was formed by their personal practical knowledge (PPK), including knowledge of the subject matter, instruction, and contexts. These findings demonstrate the usefulness of guiding L2 teacher learners to theorize from practice and suggest a framework for L2 teacher educators to promote theorizing within language teacher education courses. •Teachers were able to form their theories of learner engagement following atheorizing task.•Teacher utilized their personal practical knowledge to generate their own theories oflearner engagement.•Teachers felt empowered to have the opportunity to theorize from practice.